Perbandingan Pelaksanaan Kurikulum Bidang Pemasaran Dan Kecekapan Pelajar Antara Institusi Pendidikan Tinggi Di Malaysia - Ilangko, Ilangko (2010)

(untitled)
The ability of the undergraduates to utilise the skills acquired from their higher learning institutes in their employment sector has posed a great concern in recent years.